Eosinophil–Basophil/Lymphocyte (EB/LR) and Eosinophil–Basophil–Platelet/Lymphocyte (EBP/LR) Ratios Could Serve as Useful Additional Markers for Assessing the Severity of Wasp Allergic Reactions - Weronika Urbańska; Łukasz Szymański; Aneta Lewicka; Martyna Ciepielak; Karolina Kostrzeńska-Sęk; Andrzej Chciałowski; Sławomir Lewicki (Cells)
Wasp venom allergy can trigger severe allergic reactions, and predicting these acute responses remains challenging. This study evaluates the utility of immune system indexes, particularly the eosinophil–basophil/lymphocyte (EB/LR) and eosinophil–basophil–platelet/lymphocyte (EBP/LR) ratios, in assessing the severity of allergic reactions in patients with wasp venom allergy. A total of 61 patients with confirmed wasp venom allergy were categorized according to the Mueller scale, which classifies the severity of allergic reactions. Blood samples were analyzed for total and specific IgE levels alongside a range of hematological and biochemical parameters. This study found significant differences in the EB/LR and EBP/LR indexes between patients with mild (Mueller I–II) and severe (Mueller III–IV) allergic reactions, with higher values indicating more severe responses. However, no significant differences were observed in other immune indexes, such as the platelet-to-lymphocyte ratio, neutrophil-to-lymphocyte ratio, systemic immune-inflammation index, and systemic inflammatory response index, as well as in additional blood parameters. These findings suggest that the EB/LR and EBP/LR ratios may serve as useful markers for predicting the severity of allergic reactions in patients with wasp venom allergy. This is the first study to establish such a link, although further research with larger cohorts is necessary to confirm these results and their potential application in clinical settings.